A Project feasibility study cassava flour - Gorospe, Virginia (College of Engineering, 1993)
The food supply in the Philippines is not yet stable or adequate. In fact, the country has to import rice from other countries to make up for the balance of the supply from the demand. Natural disasters have also aggravated the situation. Aside from the staple food, Filipinos have also acquired the taste for bread and other flour-based products such that the demand for these continues to grow as the Filipino society modernizes. However, the main component of these products, the wheat flour, has to be imported since the soil here cannot sufficiently support the wheat. In a developing country like the Philippines, with its foreign currency reserves dwindling, ways had to be found and implemented to ease the burden of this importation while meeting the requirements of the people. Cassava is a root crop abundant in the Philippines. It is the staple food in some parts of the country and is very easy to cultivate even in marginal soil conditions. However, cassava is highly perishable and its production is very seasonal. It has to be processed to prolong its useful life. Cassava can be processed into flour with characteristics comparable to wheat flour. This study made on cassava flour covered the various aspects that contribute to the feasibility of establishing a cassava flour processing plant. These aspects include the market, technical, financial, social and organizational sides of the project. Information about cassava and its processing into flour were gathered through research in government and private institutions as well as interviews with people involved in the production of cassava products. Collected data were then classified and analyzed to determine the competitiveness and marketability of the product. It was established that there is a big demand for cassava flour both in the local and export market. The market for cassava flour consists of bakeshop/bakeries and consumers doing homemade flour-based products. However, it was identified as well that the main constraint in cassava processing is the inadequacy of the supply of cassava tubers which is the raw material of the flour. Under the technical study, manufacturing processes were identified and evaluated and the best alternatives were chosen. The processes selected include the following: 1) Collection and storage of raw materials, 2) Cleaning and peeling of the tubers, 3) Chipping, 4) Drying of Cassava chips, 5) Grinding, 6) Finishing and finally 7) Packing. Camarines Sur was selected as the location of the plant mainly due to its large volume output of cassava and its proximity to the target area which is Metro Manila and other urban centers in Luzon. Machine, utilities, manpower and space requirements were determined to ensure that the target daily production volume of 27,335 kilograms of cassava flour. It was shown the construction and analysis of different pro-forma financial statements that the project is financially rewarding. If the selling price of the cassava flour is fixed at P131.25 per 25-kg sack and P15 per 1-kilo pack, the income of the plant will steadily decrease since the costs of the factors of production were assumed to increase due to inflation. However, even with the constant selling rice assumption, the project is still very profitable with an average net income of P4.5 million over a 5-year period. The payback period is 2 years for the initial capital requirements of P21.5 million. The establishment of the cassava flour processing plant in Camarines Sur is socially beneficial. The major beneficiaries include: 1) Flour consumes who would realize sizable savings in using cassava flour as substitute to wheat flour; 2) Cassava farmers whose produce will be used by the plant and 3) The government which will be able to minimize dollar expenditures on wheat importation as well as increase revenue earnings from income taxes from income taxes from owners and employees of the plant. A cooperative was determined to be the best form of ownership for the processing plant/ The cooperative members will be the cassava farmers and planters who will also be the suppliers of the raw material/ Am organizational set-up was designed to support operations as well as for continuous quality improvement of the product and of the plant. The feasibility of establishing a cassava flour processing plant is indeed positive.